(3TQM bGfhf GdYbhHGJ GdYScQj (B/s - (3GdeLGdj, SejM YHO GdbGOQs; (3GdeHjVjf, Ydj eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2009)
(3ef GdeYQha Cf ddeDSSI GdYScQjI WHjYJgG GdJfXjejI GdNGUI GdeSJeOI ef WHjYI GdhXjaI GdefhWI HgG, hGdOhQ GdPj JeGQSg gPg GdeDSSI aj GdMaGX Ydi cjGf GdLeGYI hGdPhO YfgG HGdTcd GdPj jecfgG ef JMbjb eG JQej Edjg ef JbOe hGROgGQ(B. (3hbO GbJVJ gPg GdWHjYI GdJj JJejR HgG GdeDSSI GdYScQjI Gf jchf dgG fXGe NGU jTed LejY LhGfH GdMjGI GdYScQjI ; HMjK dG jbJUQ abW Ydi GdbhGYO GdJj JfXe GdCaYGd GdeTQhYI GdhGbYI aj eMjW GdMjGI GdYScQjI, Hd jJSY djTed cPdc GdCaYGd ZjQ GdeTQhYI GdJj JUOQ Yf efJSHj GdeDSSI GdYScQjI(B. (3Pdc dCf JQc GdCaYGd ZjQ GdeTQhYI GdJj bO JUOQ Yf efJSHj gPg GdeDSSI Ohf JfXje NGU hENVGYgG defXheI GdbhGYO GdYGeI aj bGfhf GdYbhHGJ, SjDOj Edi bUhQ Jdc GdbhGYO Yf JMbjb GdZGjI GdeHJZGI ef GdJfXje GdYScQj PGJg, hGdPj jJWdH bhGYO NGUI aj GdJLQje hGdYbGH JJUa HUaGJ bO dG JJhGaQ aj bhGYO GdbGfhf GdYGe(B. (3hef gfG LGAJ GdMGLI dSf bGfhf NGU ddLQGFe hGdYbhHGJ GdYScQjI djYGdL eUdMI CSGSjI eYjfI ddLeGYI, hgj eUdMI GdeDSSI GdYScQjI(B. (3hbO YQa GdeTQY GdCQOfj cZjQg aj GdJTQjYGJ GdebGQfI bGfhfG NGUG HGdLQGFe hGdYbhHGJ GdYScQjI, hPdc efP GdSfhGJ GdChdi dfThA GdOhdI GdCQOfjI, MjK UOQ Chd bGfhf NGU HGdLQGFe hGdYbhHGJ GdYScQjI YGe (B1943 (3HGSe (B"(3bGfhf GdLQGFe GdYScQjI(B" (3GdPj jMed GdQbe (B27 (3dSfI (B1943. (3hHOC JfajP CMcGeg HJGQjN (B30/1/1944(3, hSej HgPG GdGSe GfSLGeG eY JSejI bGfhf GdLRGA GdYKeGfj GdPj cGf dG jRGd eWHbkG aj Pdc GdhbJ(B. (3hHJGQjN (B26/6/1952 (3UOQ bGfhf GdYbhHGJ GdYScQj Qbe (B43 (3dSfI (B1952(3, hef Cge GdCMcGe GdJj JVefgG GdbGfhfGf GdePchQGf JTcjd GdeLGdS GdYScQjI hefMgG GdGNJUGU aj eMGceI LejY efJSHj GdbhGJ GdeSdMI, HMjK JNJU gPg GdeLGdS HGdaUd aj LejY GdLQGFe GdJj jQJcHgG GdePchQhf, hHZV GdfXQ Yf ecGf hQhOgG, hShGA ChQO GdfU YdjgG aj bGfhf GdYbhHGJ GdYScQj Ce ZjQg ef bhGfjf GdLRGA GdCNQi(B. (3hbO GSJeQ GdYed HbGfhf GdYbhHGJ GdYScQj Qbe (B43 (3dSfI (B1952 (3MJi Mqd eMqdg bGfhf GdYbhHGJ GdYScQj GdeDbJ Qbe (B30 (3dSfI (B2002(3, GdPj hVY ehVY GdJfajP HUjZJg GdOGFeI HJGQjN (B1/12/2006 (3JMJ GdQbe (B58 (3dSfI (B2006 (3hgh GdbGfhf GdSGQj GdeaYhd GdPj befG HTQMg hHjGf CMcGeg aj gPG GdcJGH(B. (3hbO LGA EUOGQ bGfhf GdYbhHGJ GdYScQj HMqdJg GdLOjOI JeGTjkG eY GdJWhQGJ GdeJSGQYI GdJj TgOJgG GdeDSSI GdYScQjI hGJSGY OGFQI fTGWGJ gPg GdeDSSI dJTed(B-(3EVGaI Edi CYeGd GdOaGY GdhWfj(B-(3GdeTGQcI aj GdbhGJ GdOhdjI dMaX GdSdGe(B. (3Ef ef Cge GdCMcGe GdNGUI GdJj fXegG gPG GdbGfhf GdfU Ydi LQGFe GdMQH GfSLGekG eY GdGJaGbjGJ GdOhdjI GdJj JOhQ aj adc GdbGfhf GdOhdj GdEfSGfj, hGdJj HGOQ GdCQOf Edi GdeUGObI YdjgG(B. (3hYQaGfkG efG HGdLejd ddeDSSI GdYScQjI GdJj faNQ HGdGfJSGH EdjgG, hCOGA dhGLH edbi Ydi YGJbfG JLGg gPg GdeDSSI hefJSHjgG, haj Xd ZjGH GdeDdaGJ GdabgjI GdeJNUUI aj GdLQGFe hGdYbhHGJ GdYScQjI, hGaJbGQ GdecJHI GdbGfhfjI dgPg GdeDdaGJ, heG fLe Yfg ef UYhHGJ Jdbj HJHYGJgG Ydi chGgd GdYGedjf aj gPG GdMbd hGdecdajf HGdCMcGe GdNGUI Hg, abO GQJCjfG(B-(3hHYO GdGJcGd Ydi Gddg(B-(3Cf fNU GdLQGFe hGdYbhHGJ GdYScQjI aj eDda NGU jJfGhd TQM CMcGe bGfhf GdYbhHGJ GdYScQj jJHYg(B-(3HEPf Gddg(B-(3eDdaGJ CNQi JYfi HTQM GdJTQjYGJ GdLRGFjI PGJ GdYdGbI hGdJTQjYGJ GdfGXeI deMceI Cef GdOhdI hGNJUGUGJgG(B.s
(3JUeje hEfJGL (B: (3ecJH OGQ GdKbGaI ddJUeje hGdEfJGL(B.s
(3HHdjhLQGajI (B: (3UaMI (B287-288.s
Keywords: (3bGfhf GdYbhHGJ GdYScQjs -- (3GdCQOfs; (3GdbGfhf GdYScQjs -- (3GdCQOfs